PEMBUKTIAN POLA PANCARAN GELOMBANG RADIO (RF) MENGGUNAKAN METODE PELACAKAN SINYAL (TRACKING) DAN APLIKASI SURFER - Kristiyana, Samuel (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2008)
Antenna is a physical structure made from metal conductor as a medium between of transmission electromagnetic wave of standing wave and as free space wave in the air which is capable of carrying information signal. The antenna structure will give specific ra-diation pattern around it. Radiation pattern cannot see with eyes but really can transmissi-on of signal so far. Radiation pattern of electromagnetic wave has understood using soft-ware application. Position of place observation and signal strength around of transmitter antenna are needed to analysis with tracking method.